Theories, Principles, and Game Elements that Support Digital Game-Based Language Learning (DGBLL): A Systematic Review - Esteban, Allan Jay (International Journal of Learning, Teaching and Educational Research, 2024)
The potential of Digital Game-Based Language Learning (DGBLL) in enhancing language learning outcomes has been demonstrated in previous studies. However, some scholars and educators maintain a skeptical perspective regarding its integration into language classrooms. Thus, this paper presents a systematic review examining the integration of DGBLL and its impact on language learning outcomes. This study examines 18 peer-reviewed articles published between 2014 and 2023 from Scopus, Web of Science (WoS), and ERIC research databases. The review explores relevant theories, principles, and game elements supporting DGBLL. It also investigates the types of digital games developed by both researchers and game developers that have already been studied, the most popular of which is serious games (83%). While the examined studies did not explicitly focus on digital game elements, they acknowledged the pivotal role of certain aspects, such as narrative, goals, rewards, and feedback, in enhancing language learning experiences. Notably, this paper affirms the positive impact of digital games on contextualized vocabulary acquisition, oral communication skills, and grammar learning, compared to conventional language teaching methods. These findings underscore the benefits of DGBLL in language education. Hence, this systematic review looks to reveal the multifaceted dimensions of DGBLL, emphasizing the theories, principles, and game elements of digital games that support the transformative potential of DGBLL for language instruction. Lastly, this paper advocates for an ongoing inquiry into the diversity of game genres and the continual refinement of frameworks to meet the evolving needs of language learners. https://doi.org/10.26803/ijlter.23.3.1